La implementación de la nueva propuesta curricular de la carrera de Educación Inicial el caso de la asignatura Metodología de la Investigación I - Mejía Cabrera, Carla Ariel (2017)
The Consejo de Educación Superior (CES), in 2013 proposed an educational reform of curricular redesign, whose purpose is to contribute to the improvement of the system of higher education of the country. In the present research work, it was possible to inquire about the problematic that has arisen, since any process of change and innovation, at the beginning implies difficulties that must be identified in order to be able to be improved and resolved. The case analysis determined the procedure and what results were obtained by implementing the new curricular proposal for the initial education career in the research methodology subject at the Salesian Polytechnic University. The research was developed through the use of observation techniques, interview and application of surveys to teachers and students who allowed to achieve the objectives and to determine the factors that influenced the process of implementation of the subject before referred.